2014
DOI: 10.1097/aap.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Guidelines for the Management of Local Anesthetic Systemic Toxicity Is Improved by an Electronic Decision Support Tool and Designated “Reader”

Abstract: Background and Objectives A hardcopy or paper cognitive aid has been shown to improve performance during the management of simulated local anesthetic systemic toxicity (LAST) when given to the team leader. However, there remains room for improvement in order to ensure a system that can achieve perfect adherence to the published guidelines for LAST management. Recent research has shown that implementing a checklist via a designated reader may be of benefit. Accordingly, we sought to investigate the effect of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
0
36
0
2
Order By: Relevance
“…Fourth, simulated LAST scenarios have demonstrated the usefulness of the ASRA Checklist 57 as a cognitive aid during LAST treatment 58 and the value of a reader to prompt adherence to recommendations. 59 An updated version of the ASRA Checklist is part of this practice advisory series. 13 The ASRA LAST smart phone app (iOS and Android) has been updated coincident with this practice advisory.…”
Section: Treatment: Evolving Paradigmsmentioning
confidence: 99%
“…Fourth, simulated LAST scenarios have demonstrated the usefulness of the ASRA Checklist 57 as a cognitive aid during LAST treatment 58 and the value of a reader to prompt adherence to recommendations. 59 An updated version of the ASRA Checklist is part of this practice advisory series. 13 The ASRA LAST smart phone app (iOS and Android) has been updated coincident with this practice advisory.…”
Section: Treatment: Evolving Paradigmsmentioning
confidence: 99%
“…Furthermore, Burden's group found that clinicians demonstrated difficulty reading a cognitive aid whilst simultaneously gathering clinical information and communicating to the team [3]. They, along with others, have described employing a designated 'reader', who enabled the leader to manage an emergency appropriately through improved team working where all team members were aware of the evolving situation, management plan, and ultimately singing from the same hymn sheet [4]. We felt this was critical and so have developed the 'reader of the cards' or 'ROC' rolea team member responsible for getting the prompt cards and bringing them to the team leader during the evolving emergency and working through the prompt cards with them.…”
Section: J Kinnearmentioning
confidence: 99%
“…1) is based on updated knowledge derived from the Third ASRA Practice Advisory on Local Anesthetic Systemic Toxicity 4 and additional insights gained through experience with the 2012 version when used during various simulation exercises. 5,6 Table 1 summarizes content and visual presentation changes.…”
mentioning
confidence: 99%
“…3,5,6 Treatment of LAST differs from other resuscitation scenarios involving cardiac arrest. Standard (1 mg) doses of epinephrine, vasoconstrictors such as vasopressin, drugs that impair cardiac contractility such as β-blockers or calcium-channel blockers, and local anesthetic antiarrhythmics are all detrimental to the local anesthetic-toxic heart.…”
mentioning
confidence: 99%
See 1 more Smart Citation